2007
DOI: 10.1097/yct.0b013e318156b77f
|View full text |Cite
|
Sign up to set email alerts
|

Patients' and Their Relatives' Attitudes Toward Electroconvulsive Therapy in Bipolar Disorder

Abstract: Although electroconvulsive therapy (ECT) is a safe and efficacious treatment, there is a widespread negative view of ECT in public and professional circles. Previous studies that reported psychiatric patients' and their relatives' feelings and attitudes toward ECT revealed generally positive results. However, there are no data focusing on bipolar patients' and their relatives' attitudes toward ECT. In this study, the perspectives of 70 bipolar patients and their 70 relatives were examined before ECT. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
17
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 22 publications
8
17
1
Order By: Relevance
“…In this study, nearly 60% of relatives and 42% of patients were given information prior to ECT. This figure for relatives is comparable to those reported from Turkey (51.4% in relatives and 32.7% in patients, respectively; Virit et al., ) and Hong Kong (58.6% in relatives and 19.8% in patients, respectively; Tang et al., ) with similar questionnaires. The higher rate of informed patients in this study may be due to the newly released national mental health law in China which came into effect in 2013.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, nearly 60% of relatives and 42% of patients were given information prior to ECT. This figure for relatives is comparable to those reported from Turkey (51.4% in relatives and 32.7% in patients, respectively; Virit et al., ) and Hong Kong (58.6% in relatives and 19.8% in patients, respectively; Tang et al., ) with similar questionnaires. The higher rate of informed patients in this study may be due to the newly released national mental health law in China which came into effect in 2013.…”
Section: Discussionsupporting
confidence: 88%
“…A separate 6‐item questionnaire was designed to collect data on adverse effects of ECT reported by patients (Table ). The questionnaires above are based on the instruments used previously (Tang et al., ; Virit, Ayar, Savas, Yumru, & Selek, ), taking into account the sociocultural factors and issues related to the practice of ECT in China. Responses for each item on the questionnaires were “agree/yes,” “disagree/no,” and “I don't know.” All assessments were conducted at 3–4 weeks after the patients' last ECT session.…”
Section: Methodsmentioning
confidence: 99%
“…A survey led by Malekian and colleagues in Iran found that patients' attitudes towards ECT became more positive after completion of ECT courses, independent of treatment outcome [106]. Similar results were found in a sample of bipolar patients and their families in Turkey [107]. If anything, these results indicate that individuals who have been exposed to ECT, either as patients or as family members of a patient receiving ECT, tend to have more positive opinions of the treatment.…”
Section: Public Opinion and Attitudessupporting
confidence: 51%
“…Apart from memory impairment, other adverse effects of ECT were reported by patients in 15 studies (Vergese et al 1968;Gomez 1975;Freeman and Kendell 1980;Malcolm 1989;Riordan et al 1993;Tharyan et al 1993;Ishimoto et al 2000;Taieb et al 2001;Tang et al;Benbow and Crentsil 2004;Philpot et al 2004;Rush et al 2007;Virit et al 2007;Malekian et al 2009). Other common side effects following ECT included muscle aches and pains (1-94%), confusion (20-65%), headache (1-55%) and nausea or vomiting (0.5-25%).…”
Section: Experience Of Different Aspects Of the Ect-procedurementioning
confidence: 92%
“…Recall of information seemed to worsen with longer courses and greater number of treatments (Greening et al 1999). Moreover, some of these studies had also reported that relatives were much more likely than patients to believe that they had received adequate information Tang et al 2002;Rajkumar et al 2006;Virit et al 2007;Rajagopal 2008). This again raises the possibility that patients might have forgotten some of what was explained prior to treatment, due to post-ECT memory loss.…”
Section: Details Of Studies Includedmentioning
confidence: 93%